Chinese People and the Others - Jarkko Haapanen (Journal of China and International Relations, 2019)
The May Fourth Movement (1917-1921) has always been an important part of the official historical narrative of the Chinese Communist Party. Today, the Movement is often celebrated as being closely connected with the emergence of modern Chinese patriotism and nationalism in contemporary China. In the 21st century, Chinese nationalism has voiced more assertive overtones with a tendency to glorify Chinese imperial history. What is more, contemporary Chinese nationalism often adopts a negative attitude towards foreign ideas and thought trends. This article discusses the differences between contemporary Chinese nationalism and the May Fourth Movement nationalism by examining the argumentation structures wherein the concept of nationalism was used during the May Fourth period. The article shows that the concept was, in fact, given primarily a negative meaning in the May Fourth context. The article shows that, in May Fourth journals, nationalism was associated with imperialism, capitalism, and Darwinism, which were presented as destructive ideas that were responsible for the First World War. Unlike the radical Chinese nationalists of the 21st century, May Fourth authors supported a cosmopolitan spirit and international cooperation. The desire to strengthen and develop China involved dreams of creating an international operational environment based on equality and cooperation, instead of aggressive power politics.